2014
DOI: 10.1159/000356531
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Cognitive Impairment in Parkinson's Disease: A Role for Inflammation and Immunomodulation?

Abstract: The etiology of Parkinson's disease (PD) is complex and not fully understood, most probably because of the multiplicity of factors involved. Inflammatory and abnormal immune responses have been hypothesized to play a crucial role in PD. Not only in the brain, but also peripherally, inflammation is believed to contribute to the onset and progression of the neurodegenerative process seen in PD. Furthermore, increased inflammatory responses have been described both in the brain and peripheral blood of PD subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…For example, TV viewing has been associated with a prothombotic/inflammatory state (i.e., interleukin 6, C-reactive protein, and endothelial function) 12,33,34 which, in turn, has been linked with progression of COPD, 35 Parkinson disease, 36 and sepsis mortality, 29 perhaps due to inactivity associated with prolonged TV viewing. Similarly, TV viewing has been associated with lower cardiorespiratory fitness 24 and muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TV viewing has been associated with a prothombotic/inflammatory state (i.e., interleukin 6, C-reactive protein, and endothelial function) 12,33,34 which, in turn, has been linked with progression of COPD, 35 Parkinson disease, 36 and sepsis mortality, 29 perhaps due to inactivity associated with prolonged TV viewing. Similarly, TV viewing has been associated with lower cardiorespiratory fitness 24 and muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of being able to block inflammation at any point during the disease might have benefits for non-motor symptoms [13, 39]. Subsequently, others have shown that TNF [16] and c-reactive protein (CRP), classic companion biomarkers of inflammation, were correlated with fatigue [15], depression [40], cognition [41], and hallucination [42] in PD patients and plasma solTNF receptors were correlated with cognitive impairment in PD patients [17].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta‐analysis reports that pro‐inflammatory cytokines such as IL‐1b, IL‐6, and TNF, but also others such as IL‐10 (known for its anti‐inflammatory actions) and RANTES (known for its chemotactic properties) are increased in PD, suggesting a complex ongoing regulation of the immune response (Qin, Zhang, Cao, Loh, & Cheng, ). Interestingly, these soluble markers were correlated with non‐motor symptoms, which are proposed to precede motor symptomatology (Kohler, Krogh, Mors, & Benros, ; Pessoa Rocha, Reis, Vanden Berghe, & Cirillo, ). In particular, depression in PD patients has been associated with increase of several cytokines, although there is no clean consensus of which factors are up or down in PD patients relative to healthy controls.…”
Section: Soluble Immune Biomarkers May Help Stage Disease and Correlamentioning
confidence: 99%